From an emic perspective: exploring consent in forced marriage law - Sowey, Helen (The Australian and New Zealand journal of criminology, 2018)
Forced marriage was criminalised in Australia in March 2013, putting the issue on the agenda of policy-makers and social service providers. Increasingly, however, it is being recognised that criminal laws alone cannot address the practice; protective and preventative strategies are also needed. This paper argues that strategies to address forced marriage will be most effective if they are informed by contextualised and emic understandings of the phenomenon, that is, by the perspectives of individuals, families and communities who are directly affected by forced marriage. Primary research is required to obtain such perspectives. Research into forced marriage in Australia is still in its infancy, and primary research is almost non-existent. This paper, then, looks to primary research from the UK and other comparable Western multicultural nations, offering a critique of this body of literature before drawing out what is revealed about why marriages are forced, how marriages are forced, and what people in forced marriage situations want. The implications of criminal prosecution are then considered in light of this emic understanding. The legal definition of forced marriage hinges on the concept of consent: it is consent that distinguishes an arranged marriage from a forced one. In the UK, the notion of consent has been robustly problematised. However this is not the case in Australia at present, and this paper critiques the value of the concept of consent given the social contexts of forced marriage described above. The implications of this critique for the application of Australia’s forced marriage law are then considered. Finally, from a place of contextualised and emic understanding of forced marriage, this paper considers how protective and preventative strategies might be enhanced.